MOTIVASI KERJA DAN KINERJA PENYULUH PERTANIAN DI KABUPATEN BERAU (Work Motivation and Performance of Agricultural Extension Workers in Berau Regency) - MANSUR TANCA; MUHAMMAD JAMAL AMIN; SUDIRAH SUDIRAH (Universitas Mulawarman (University of Mulawarman), 2022)
Agricultural extension workers have work performance that should be increased. This illustrates that it is needed the increase of work motivation and performance of agricultural extension workers. This study aimed to analysis the work motivation and performance of agricultural extension workers in Berau Regency. The analysis was done descriptively. The work motivation of agricultural instructors could be assessed from work performance, recognition from others, responsibility, opportunities for advancement, salary/wages, and work relations. The performance of agricultural extension workers could be viewed from the preparation of agricultural extension, implementation of agricultural extension, evaluation and reporting.